Relevance of document types in the scores’ calculation of a specific field-normalized indicator: Are the scores strongly dependent on or nearly independent of the document type handling? - Haunschild, Robin; Bornmann, Lutz (Scientometrics, 2022)
Although it is bibliometric standard to employ field normalization, the detailed procedure of field normalization is not standardized regarding the handling of the document types. All publications without filtering the document type can be used or only selected document types. Furthermore, the field-normalization procedure can be carried out with regard to the document type of publications or without. We studied if the field-normalized scores strongly depend on the choice of different document type handlings. In doing so, we used the publications from the Web of Science between 2000 and 2017 and compared different field-normalized scores. We compared the results on the individual publication level, the country level, and the institutional level. We found rather high correlations between the different scores but the concordance values provide a more differentiated conclusion: Rather different scores are produced on the individual publication level. As our results on the aggregated levels are not supported by our results on the level of individual publications, any comparison of normalized scores that result from different procedures should only be performed with caution.